Loot boxes are gambling-like elements in video games with harmful potential: Results from a large-scale population survey. (November 2020) - von Meduna, Marc; Steinmetz, Fred; Ante, Lennart; Reynolds, Jennifer; Fiedler, Ingo
Abstract: Loot boxes are a growing feature in the business models of video game production. They can be obtained through in-game purchases ranging from $0.5 to over $100 and contain chance-based virtual items that may offer an advantage in a video game making them gambling-like products. This study seeks to fill the current research gap with the analysis of a representative survey among 46, 136 Internet users. Within this sample 1508 are Pay2Win users and more specifically, 586 of those Pay2Win users (38.9%) purchase loot boxes. Loot box users are an average age of 36.7 years and are predominantly male (55.3%). A high number (45.9%) meet the criteria for problem gambling measured by the PGSI. A significant negative age-effect exists, and a lower level of education has strong positive impacts on loot box participation. Loot box participation and purchasing frequency are positively associated with gambling problems and we argue that loot box purchasers are at risk of experiencing gambling problems. Highlights: Over a third (38.9%) of Pay2Win users purchase Loot Boxes. It exists a significant negative age-effect on Loot Box participation. A lower level of education has strong positive impacts on buying Loot Boxes. A high number (45.9%) of Loot Box users meet the criteria for problem gambling. There is a positive association of Loot Box participation with gambling problems.